Early college program implementation and growth: a collaborative initiative by a state university - Yavuz, Olcay; Milburn, Trudy (Concurrent Enrollment Review, 2025)
This article explores a collaborative initiative undertaken by a state university aimed at implementing and expanding an Early College Program. The conceptual framework, practical strategies, collaborative efforts and background of this initiative are presented. With a focus on improving college access for all, the article introduces the university's efforts to promote an inclusive Early College Program accessible to high-need students in particular. This collaborative approach highlights the importance of fostering collaboration among both internal and external partners of Institutions of Higher Education (IHE). By sharing insights into the program design and implementation, the article aims to inspire similar initiatives and contribute to the ongoing dialogue promoting early college experiences for all.
Keywords: Conceptual framework; Focus (optics); Focus group; Higher education; Program evaluation; State (computer science); dept.aa; dept.edl

Impact of supervision and evaluation on the professional development of school-based speech-language pathologists - Brown, Jacqueline; Trombly, Christopher; Roitsch, Jane (Perspectives of the ASHA Special Interest Groups, 2025)
Keywords: American Speech-Language-Hearing Association; Asha; Developmental psychology; Language development; Linguistics; Medical education; Medicine; Pedagogy; Professional development; Psychology; dept.edl

“Community hoarding”: a further complication for education research? - Arafeh, Sousan (2025)
Keywords: Computer science; Hoarding (animal behavior); Medicine; dept.edl

Polish and Indian teachers’ self-efficacy and attitudes towards inclusion of children and youth with disabilities in regular classrooms - Ćwirynkało, Katarzyna; Parchomiuk, Monika; Gregory, Jess; Ravi, Sunitha; Krishnamurthy, Sita (International Journal of Inclusive Education, 2025)
Keywords: Developmental psychology; Inclusion (mineral); Mainstreaming; Mathematics education; Pedagogy; Psychology; Self-efficacy; Social psychology; Sociology; Special education; Teachers; attitudes towards inclusion; dept.edl; inclusion; self-efficacy; students with disabilities

The Problem of Practice Dissertation: Matching Program Goals, Practices, and Outcomes - Belzer, Alisa; Axelrod, Tali; Benedict, Cathleen; Jakubik, Tara; Rosen, Michelle; Yavuz, Olcay (The EdD and the Scholarly Practitioner(HC), 2016)
The purpose of this book is to highlight the efforts of the members of the Carnegie Project on the Education Doctorate (CPED) to prepare Scholarly Practitioners in the field of education leadership. The volume is edited by Jill Alexa Perry, Executive Director of CPED, a consortium of 86 schools of education in the US, Canada and New Zealand. CPED is a collaboration of faculty working together since 2007 to re‐envision professional practice preparation in education. Contributing authors include faculty and graduates from CPED‐influenced programs. Faculty members highlight the need to rethink and strengthen all aspects of doctoral level preparation for practitioners, the expanded and enhanced role of research, inquiry and the dissertation in practice, and discuss the implications these changes have on university schools of education. Students and graduates, who face pressing educational issues in their daily lives, reflect on the impact their EdD program has had on their professional practice.
Keywords: dept.edl

On Becoming a Leader - Gregory, J.L. (Educational Leadership: Perspectives on Preparation and Practice, 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedag...
Keywords: dept.edl

Diversity & Cultural Competence - Labas, G; Gregory, J.L. (Educational Leadership: Perspectives on Preparation and Practice, 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedag...
Keywords: dept.edl

Research and Program Evaluation - Haynes, N.M.; Gregory, J.L.; Diffley, W.J. (Educational Leadership: Perspectives on Preparation and Practice, 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedag...
Keywords: dept.edl

Editorial: Further work on educational leadership and social justice - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

The adaptive challenge of social justice in educational leadership - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Urban high school faculty members speak up: what they need from a school counseling program from school counselors and principals - Graf, Eric; Yavuz, Olcay (Journal of Educational Leadership and Policy Studies, 2023)
There is a growing emphasis to improve every student's academic, social-emotional, and career and college development as schools strive to design and deliver comprehensive counseling programs that support students' development in these areas. The purpose of this study is to explore a large urban high school teachers' counselors and admins' perspectives on improving a high-poverty urban school's counseling services to extend school leaders' and counselors' knowledge about delivering effective school counseling programs as, ultimately, success lies with an effective principal and school counselor partnership. Particularly, data from our study will allow urban school principals and school counselors to identify the high and low program needs of urban students to become college, career, and life ready. The next set of comparisons was conducted for social-emotional needs. Like academic development needs, the entire ANOVA summary tables showed non-significant differences. The findings indicated that some responses varied significantly across (1) special education faculty, (2) regular classroom teachers and (3) school counselors in terms of rating of students' counseling needs. School leaders and school counselors can apply the findings of this study to create systemic and comprehensive student services in their schools. Particularly, school leaders and counselors can apply the results in decision-making, discussions, and time allocation in prevention/education versus reactive/responsive academic and counseling services.
Keywords: Administrator Attitudes; Administrator Role; Career Readiness; College Readiness; Connecticut; Counselor Attitudes; Counselor Role; Educational Needs; High School Teachers; Poverty; Principals; School Counseling; School Counselors; Social Emotional Learning; Student Needs; Teacher Attitudes; Urban Schools; dept.edl

Targeted professional development strategies to increase teachers’ efficacy for educating students with special needs - Yavuz, Olcay (Çağdaş Yönetim Bilimleri Dergisi, 2020)
There is a significant increase in the number of students with disabilities. However, many general education teachers report that they feel ill-equipped to educate a classroom of students with diverse special education and learning needs. In this qualitative study, the structured focus group interviews were conducted to determine the PD opportunities and characteristics that general education teachers perceive to influence their sense of self-efficacy for educating students with special needs. The results of the focus group discussions revealed that there are several targeted professional development strategies to increase teachers’ efficacy for educating students with special needs. This study makes recommendations for the research supported professional development activities, focused on educating students with special needs, provided to general education teachers.
Number: 2
Keywords: dept.eco; peer-reviewed; ⛔ No DOI found

Quantitative explorations of teacher self-efficacy towards students with special needs: Research Article - Arterbery, Denise Hart; Yavuz, Olcay (FIRE: Futuristic Implementations of Research in Education, 2020)
Teacher self-efficacy has been linked to positive student outcomes. This quantitative research study aimed to examine the mindsets and behaviors of regular education teachers concerning their ability to educate students with special needs. The modified Teacher Self Efficacy Survey was administered to general education teachers. Data revealed that general education teachers feel less efficacious for educating students with special needs in the areas of engagement, instructional strategies, and classroom management. This study makes recommendations for professional development, focused on educating students with special needs, provided to general education teachers. Particularly, the findings speak to the need for a more diverse, flexible, and comprehensive approach to implement teacher professional development activities to improve the achievement of students with special needs.
Number: 1
Keywords: Classroom Management; dept.eco; peer-reviewed

Behavior Management: Traditional and Expanded Approaches - Haynes, Norris M. (UPA, 2012)
Keywords: dept.eco

Higher education and the great resignation: a crisis of compounded inequities - Rivers, Yevgeniya (2023)
Keywords: SCSU-student; dept.edl

Self-Identification in Black, Red, Brown, and White: A clarion call to address medical racism in Native American communities - Boudreaux, Mary (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
This chapter provides a brief autobiographical account of her multiethnic and racial background as a Louisiana Creole in south Louisiana. The author points out that among all racial and ethnic groups in the United States, Indigenous people are the only ones that require some form of lineal Native American descent or blood quantum. The chapter provides an ancestry account of two American Indian tribes along the bayous of south Louisiana, the Chitimacha, and the United Houma Nation. While one federally recognized tribe has attempted to remove all relations to individuals of Black, Negro, or African American descent, the other has closed enrollment to new members (despite lineal descent), with the unifying factor among these communities being establishing progenitors. Finally, the author articulates how lack of access to resources related to issues such as COVID-19 has perpetuated the historical legacy of medical racism in tribal and underserved communities in the United States.
Keywords: COVID-19; Medical racism; Native American; Tribal communities; dept.edl

Group Dynamics: Basics and Pragmatics for Practitioners - Haynes, Norris M. (University Press of America, 2012)
Keywords: Social groups; Group facilitation; dept.csp; dept.eco; faculty_collection

Sabbatical leave report. - Gregory, Jess L. (2019)
Sabbatical to write textbook: "School leadership for learning : learning theory to improve professional practice".
Keywords: dept.edl; faculty_collection; sabbatical_report

Mobile Learning: Perspectives on Practice and Policy - Herro, Danielle; Arafeh, Sousan; Ling, Richard Seyler; Holden, Chris (Information Age Publishing, Inc., 2018)
Keywords: Mobile communication systems in education; United States; United States; Internet in education; dept.edl; faculty_collection

Constructing Your Dissertation: A Guide for Students as They Begin Their Doctoral Research - Gregory, Jess L. (CreateSpace, 2016)
Keywords: Authorship; Academic writing; Dissertations; Academic; dept.edl; faculty_collection

Educational Leadership: Perspectives on Preparation and Practice - Haynes, Norris M.; Arafeh, Sousan; Magagula, Cynthia McDaniels (University Press of America, ® Inc., 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedagogical and experiential learning models as well as provocative new paradigms of their own to help prepare leaders and reinforce leadership effectiveness.
Keywords: Educational leadership; School management and organization; dept.edl; faculty_collection

Comparative Perspectives on International School Leadership: Policy, Preparation, and Practice - Magno, Cathryn S. (Routledge, 2013)
Through a multi-country study, Comparative Perspectives on International School Leadership examines the current global spread of educational leadership, occurring rapidly and widely. Exploring five international case studies of leadership policy, preparation, and practice under the framework of policy borrowing and adaptation, Magno attempts to understand and account for commonalities and differences across country contexts. Rather than assuming a particular model or theory to leadership is best, Comparative Perspectives on International School Leadership takes a policy-orient
Keywords: Cross-cultural studies; Cross-cultural studies; School management and organization; Educational leadership; dept.edl; faculty_collection

A Handbook of Statistics and Quantitative Analysis for Educational Leadership - Mulcahy, John W. (University Press of America, 2009)
This handbook is an approachable reference for all levels of educational leadership. The topics are presented with a clarity that makes the mathematics accessible, even if the reader has not had prior training in research methods or statistics.
Keywords: School management and organization; Statistical methods; Statistical methods; Educational leadership; dept.edl; faculty_collection

Curriculum Alignment: Research-Based Strategies for Increasing Student Achievement - Squires, David A. (Corwin Press, 2009)
Keywords: Curriculum planning; Standards; United States; United States; Education; United States; Educational accountability; United States; Educational tests and measurements; dept.edl

Aligning and Balancing the Standards-Based Curriculum - Squires, David A. (Corwin Press, 2005)
Keywords: Curriculum planning; Standards; United States; United States; Competency-based education; United States; Education; dept.edl; faculty_collection

The Power of Poetry for School Leadership: Leading with Attention and Insight - Richardson, Lystra M. (Scarecrow Press, 2003)
Keywords: Poetry; Study and teaching; United States; United States; Educational leadership; dept.edl; faculty_collection

New Pythian Voices: Women Building Political Capital in Ngos in the Middle East - Magno, Cathryn S. (Routledge, 2002)
Keywords: Middle East; Middle East; Feminism; Middle East; Non-governmental organizations; Political activity; Women; dept.edl; faculty_collection

Effective Schools and Classrooms: A Research-Based Perspective - Squires, David A.; Huitt, William G.; Segars, John K. (Association for Supervision and Curriculum Development, 1983)
Keywords: School management and organization; Classroom management; Academic achievement; dept.edl; faculty_collection

Teachers’ Attitudes Towards Inclusive Education: a Cross-National Exploration - Charitaki, G.; Kourti, I.; Gregory, J.L.; Ozturk, M.; Ismail, Z.; Alevriadou, A.; Soulis, S.-G.; Sakici, Ş.; Demirel, C. (Trends in Psychology, 2022)
The study aims to suggest a model for attitudes towards inclusive education that will yield a good fit across different countries. Moreover, we aim to explore the effect of years of teaching experience, educational work level of teachers, and the highest degree completed by teachers on teachers’ attitudes towards inclusion across different countries. A demographic scale and the ATTAS-mm were applied to 908 teachers employed in schools of general education or who offered parallel support and/or resources in five different countries (Greece, the UK, the USA, Malaysia, and Turkey). CFA suggested a 4-factor solution, which included the cognitive, affective, and behavioral factors that have been previously introduced by Gregory and Noto (2012), and a fourth factor, labeled overall attitudes towards teaching all students. In the cognitive factor, the UK had the most positive attitudes. TU, MA, and GR enrolled in the same cluster, and the USA had the least positive attitudes. In the affective factor, GR had the most positive attitude. MA and the USA enrolled in the same cluster and TU and the UK had the least positive attitudes. A similar pattern is observed for the behavioral factor with GR having the most positive attitude. TU and MA enrolled in the same cluster, and the USA and the UK had the least positive attitudes. Finally, years of teaching experience, educational work level, and the highest degree completed have a significant effect on teachers’ attitudes towards inclusion in all countries. Providing feedback for future research is the focal point of the discussion part. © 2022, Associação Brasileira de Psicologia.
2 citations (Crossref) [2023-10-31]
Keywords: Affective; Attitudes; Behavioral; Cognitive; Inclusive education; Teachers; dept.edl; peer-reviewed

Improving Psychological and Emotional Well-Being of the First-Year College Students - Robinson, Dyan; Yavuz, Olcay (FIRE: Futuristic Implementations of Research in Education, 2021)
Almost half of the students who begin college are not retained at the institution in which they began. The purpose of this research was to explore the perceptions of first-year college students to improve their psychological and emotional well-being. This quantitative study utilized the College Student Mentoring Scale that includes two interrelated constructs which are, Psychological and Emotional Support and The Existence of a Role Model. The research found that multiple factors impact first-year students' perceptions of their psychological and emotional well-being. Additional findings indicated that response levels were highest for The Existence of a Role Model. It is the intention that this study will add to the somewhat limited research on improving the psychological and emotional well-being of first-year college students in higher education. Also, it will assist in future policies and practices by providing a foundation of the components that influence first-year student success through improving the effectiveness of peer mentoring programs.
Number: 2
Keywords: dept.com; dept.edl; dept.fye; first-year college students; peer-reviewed; ⛔ No DOI found

Building bridges of empowerment to improve students' achievement: A dicussion of alternative models - Hayford, B.K. (Multiculturalism in the Age of the Mosaic: Essays in Honor of Rudolph G. Wilson, 2010)
Journal Abbreviation: Multicult. in the Age of the Mosaic: Essays in Honor of Rudolph G. Wilson
Keywords: dept.edl

Improving access and equity in tertiary education in Ghana: The role of private tertiary educational institutions - Hayford, B.K. (Multiculturalism in the Age of the Mosaic: Essays in Honor of Rudolph G. Wilson, 2010)
Journal Abbreviation: Multicult. in the Age of the Mosaic: Essays in Honor of Rudolph G. Wilson
Keywords: dept.edl

Assessment research - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl

Commonalities And Differences Of District Stories Of Using Curriculum To Improve Achievement - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl

Curriculum: District stories of a path to improved achievement - Squires, D.A. (Nova Science Publishers, Inc., 2014)
A curriculum is not known to improve academic achievements. This book offers case studies of three Connecticut districts of high, medium and low socio-economic status, three districts from a national sample that won the prestigious Booker prize mainly representing low SES districts, and 10 districts that have implemented a Balanced Curriculum with a sample of various SES districts from high to low. All of them have used their curriculum as the vehicle toward improved achievements. The districts studied have four common themes, represented by the acronym "ASIA", for Alignment, Structure and Stability, Implementation and Infrastructure, and Assessment. All districts aligned their curriculum to state standards and assessments. They had a structure for the curriculum and had stability at the superintendent's position. The districts applied a lot of effort and attained results from implementing the curriculum and developing the infrastructure to support implementation, and they finally incorporated frequent district-wide assessments into their design. The book documents the subsets of these four areas that were present in most districts that might help other districts to replicate the findings. Research in the four areas is also documented. This book demonstrates through the case studies that it is possible to use curriculum as a framework for raising test scores. This is not normally thought of as a path to improved achievements. The fact that districts from a wide range of socio-economic statuses have used their curriculum to improve achievements demonstrates that a wider application of this direction could yield positive results for other districts. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev. Pages: 199 Publication Title: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl

Curriculum structure and district leadership stability - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl

Implementation: A model for making implementation plans - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl

Other Popular Avenues For District Improvement: Using Asia To Assess Their Power - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
In reading through the district stories about using curriculum as a framework for improvement, many innovations were interwoven into ancillary efforts for curriculum development. As these are part of the stories of district curriculum development, we thought that discussions of these "ancillary efforts" were important. The innovations considered in this chapter are: Power standards, Professional learning communities, Common assessments, Data-driven decision making, and Walk-through's. We will consider these as if they were being implemented alone, and assess their power to produce student achievement gains using the ASIA framework. References to the district stories will be given. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl

Planning Curriculum Development and Implementation - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Working with districts over the past 15 years to write and implement a balanced curriculum has been a wonderful experience; especially as so many of the districts that I worked with saw their student achievement improve (Squires, 2013). Now, thousands of students are getting better results because the curriculum was developed and well implemented using the Balanced Curriculum model. As is evident by the chapters about other school districts, the balanced curriculum is not the only way to get improvement, as the districts highlighted in this book also used curriculum as a framework for improving achievement. In this chapter I will highlight lessons learned along the way about developing and implementing curriculum. Using ideas described in chapter 6, we will highlight what major roles need to know and be able to do in planning, developing and implementing curriculum. For those with experience of working within a district, this will give one model to compare your district's curriculum writing and implementation efforts. We begin by dividing the effort into three areas: planning, writing, and implementing curriculum. To plan, we create a planning team to guide the process of writing and implementing curriculum. We don't separate curriculum writing from curriculum implementation because how the curriculum is implemented will, in part, depend on how the curriculum was written. We believe that such curriculum development and implementation has the potential to last over several years, and we believe that such an effort needs people who can stay the course over those years, so the effort is not wasted. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl

The alignment research - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl

The balanced curriculum model - Squires, D.A. (Curriculum: District Stories of a Path to Improved Achievement, 2014)
Journal Abbreviation: Curric.: Dist. Stories of a Path to Improv. Achiev.
Keywords: dept.edl

Plagiarism as a social contract, a new way to approach plagiarism - Gregory, Jess L. (Journal of Academic Ethics, 2021)
Most cases of plagiarism involve a power differential where not every person has the same ability to enter into a social contract. A social contract requires that each party understands the expectations or norms of the contract, has a voice in setting or changing the norms and has the ability to exit the contract. If those with less power want to gain power then they have to engage in activities bound by norms set by others with little or no ability to exit and no voice. Even if one determines that it is an option to choose a role that requires academic writing, even at the earliest grades, then the social contract demands a shared norm of what constitutes correct behavior. This study reviewed the abstracts of articles indexed in Google Scholar from 1999–2019 through the lens of integrative social contract theory (ISCT) and found, in the case of plagiarism, an existing consensus of correct behavior does not exist. Recommendations for establishing a social contract conclude the article.
3 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103650269
Keywords: dept.edl; peer-reviewed

Learning in the time of COVID-19: capitalizing on the opportunity presented by the pandemic - Trombly, Christopher E. (Journal of Professional Capital and Community, 2020)
Purpose: This paper addresses the current disruption in the educational status quo ante that has been caused by the worldwide outbreak of COVID-19. Its purpose is to suggest how practicing educators, their professional associations and the university-based researchers with whom they partner might capitalize on the unanticipated opportunity to impact education policy that the pandemic presents. Design/methodology/approach: The author draws upon his own preparation and experiences – first as a long-time practitioner in the elementary and secondary school setting, then as a university professor – to offer insights and suggestions to practicing educators, their professional associations and the university-based researchers with whom they partner. Findings: Despite the unexpected challenges that the COVID-19 pandemic has presented to educators – challenges to which educators around the globe have risen admirably – the current crisis also affords practicing educators, their professional associations and the university-based researchers with whom they partner to change the status quo ante for the better. Originality/value: The particular value of this piece is twofold: its analysis of the impact of this unanticipated crisis upon education by an author who has served both in the elementary/secondary setting and at the university level, and its assertion that educators must avail themselves of this once-in-a-lifetime opportunity to change the educational status quo ante for the better. © 2020, Emerald Publishing Limited.
17 citations (Crossref) [2023-10-31] WOS:000546450400001
Keywords: Collaboration; Community; Professional judgment; dept.edl; peer-reviewed

The advantages of inclusion for students with learning-disabilities - Brucker, PO (Journal of Learning Disabilities, 1994)
4 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1994PN46500006
Keywords: dept.edl

Imaging girls: visual methodologies and messages for girls' education - Magno, Cathryn; Kirk, Jackie (Compare, 2008)
This article describes the use of visual methodologies to examine images of girls used by development agencies to portray and promote their work in girls' education, and provides a detailed discussion of three report cover images. It details the processes of methodology and tool development for the visual analysis and presents initial 'readings' of the selected images. This initial study highlights the relevance of image analysis to the field of gender, education and development and of critical reflection on the different messages and meanings inherent in images of girls and girls' education which relate to complex questions of power and privilege, position and post-coloniality. The authors recommend that within development agencies education and communication specialists work together to develop more sophisticated processes for image selection, review and feedback, and that researchers in the field further engage with visual methodologies to inform current theories of girlhood, education, schooling and empowerment.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-326-190-434-512 tex.type: [object Object]
Keywords: Education; Girls; Images; Methodology; Representation; dept.edl

Teaching in transition: Examining school-based gender inequities in central/southeastern Europe and the former Soviet Union - Magno, Cathryn; Silova, Iveta (International Journal of Educational Development, 2007)
In the last decade, gender equity has become one of the most prominent issues in education reform efforts worldwide. Yet, questions of gender equity have received very little attention in the education reform efforts in the post-socialist countries during the transition period. Focusing on the political, economic, and social changes of the 1990s, this article examines school-based gender equity as it is treated in textbooks, curriculum, teacher attitudes, school environment, leadership and tracking. The article presents gender-sensitive strategies for reform and explores how existing `genderneutral' education practices detrimentally affect gender equity in schools, providing country-specific examples. The article concludes with recommendations for teaching in transition, given the education sphere's strong potential to redress gender inequities. (c) 2006 Elsevier Ltd. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/134-656-786-395-500 tex.unique-id: [object Object]
Keywords: Education reform; Eurasia; Europe; Gender equity; Post-socialist transition curriculm; curriculum; dept.edl; education reform; equity; gender disparity; gender relations; gender role; peer-reviewed; post-communism; social change; teaching; transitional economy

The role of ego threat in professional growth: Fulfilling the ethical intentions of the SEED Model - Gregory, Jess L.; Mebane, Karreem A. (Educational Practice and Theory, 2020)
Schools and education in general have made an implicit and, we would assert, explicit promise to society to educate all the children in their care. Unfortunately, there are achievement gaps that illustrate how schools have broken this promise. Teacher evaluation and other accountability measures have been heralded as the answer to this problem. Educator ego threat impedes the implementation of goal-driven teacher evaluation models and, thus, ethical questions arise. To realize the noble goals of educator evaluation, leaders must attend to ethical concerns and to the human aspects of ego threat.
0 citations (Crossref) [2023-10-31] tex.ids: gregoryRoleEgoThreat2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85090739249 type: Article
Keywords: Educational leadership; Ego threat; Goal-setting models; Teacher evaluation; Teacher performance; dept.edl; dept.rec; peer-reviewed

Super teachers - Corde, Salvatore J. (Phi Delta Kappan, 2012)
Superintendents have the responsibility to engage in the act of teaching their colleagues what they have learned about the most important work of school districts-ensuring high student achievement. They also must provide strong leadership that will foster and nurture powerful learning communities.
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000301306000008
Keywords: dept.edl

Exploring the impacts of school reforms on underrepresented urban students’ college persistence - Yavuz, Olcay (Educational Research and Evaluation, 2016)
This longitudinal quantitative study investigates how participation in the Comprehensive College Readiness Access and Success Program (CCRASP) affects underrepresented urban students’ college persistence. Results revealed that CCRASP participation was associated with higher percentages of students enrolling in both 2- and 4-year colleges as sophomore students. As school leaders and policy makers seek to make all urban students college and career ready, these findings further solidify current urgencies to re-visit K–12 student academic and counselling services. It also provides school leaders and educators with practical information and reform ideas to improve underprivileged students’ persistence and success. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
3 citations (Crossref) [2023-10-31] Citation Key Alias: pop00196 tex.type: [object Object]
Keywords: Research-supported school reforms; at-risk students; college persistence; dept.edl; programme evaluation

Curriculum mapping in higher education: a case study and proposed content scope and sequence mapping tool - Arafeh, Sousan (Journal of Further and Higher Education, 2016)
Best practice in curriculum development and implementation requires that discipline-based standards or requirements embody both curricular and programme scopes and sequences. Ensuring these are present and aligned in course/programme content, activities and assessments to support student success requires formalised and systematised review and development processes. These processes are not always in play in higher education, however. Using a descriptive qualitative case study strategy, this article shares how policy outcomes within intermediate and superintendent certification, sixth-year and Ed.D. doctoral courses and programmes at a state university were reviewed, mapped and assessed using an evidence-based curriculum analysis model and tool that mapped standards and outcomes from course syllabus data. Strengths and weaknesses of this approach are discussed and it is suggested that the field might benefit from a curriculum mapping and analysis method that also considers content coverage. A Course-Level Content Scope and Sequence Mapping Tool, developed to map content scope and sequence alongside standards or outcomes mapping, is presented for consideration and testing. The ability to assess and improve curriculum is only as good as the conceptual frameworks, methods and tools available. This critical case study is one effort to advance the field by drawing attention to the importance of curricular content mapping. The study should be of interest to higher education staff, researchers and accreditors concerned with postsecondary programmes and their curricular scope and sequence coherence, quality and improvement. © 2015 UCU.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/115-122-192-888-441 tex.type: [object Object]
Keywords: Curriculum; content; content mapping; curricular content; curricular scope and sequence; curriculum mapping; curriculum mapping tool; dept.edl; educational leadership; higher education; policy; programme coherence

Provoking perspectives of creativity and innovation in leadership: innovation, accountability, and the human side of change - Gregory, Jess L (Journal of Leadership Studies, 2016)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/056-562-317-960-189 tex.type: [object Object]
Keywords: dept.edl; peer-reviewed

Building Social Capital from the Inside Out: Leveraging Intrapower (Personal Capital) - Haynes, Norris M. (Social Capital and Community Well-Being : The Serve Here Initiative, 2016)
In this writer’s view, the building of social capital starts with the development of personal individual capital. The author posits that an individual may not be optimally effective in building meaningful social relationships and networks, or in influencing results in one’s community that serve the individual and others well, unless the individual has the prerequisite personal attributes and skillsets to do so. Therefore, in this chapter, the author identifies four key personal capital attributes that he sees as foundational to the building of social capital from the inside out. The dynamic synergistic interface among these four core attributes (Control, Empathy, Awareness, and Resolve), is referred to in this chapter as “Intrapower that is seen as a potent facilitative force in the effective building of social capital.
Citation Key Alias: lens.org/047-450-620-848-381
Keywords: Achievement motivation; Civic engagement; Mindfulness; Resilience; Self-awareness; Self-control; Self-regulation; Social & emotional; Youth development; dept.edl

The balanced curriculum model: Description and results - Squires, David (SAGE Open, 2013)
The Balanced Curriculum is a web-based tool that school districts use to create, align, assess, and manage their curriculum development and implementation. The courses are divided into time-bound units with significant tasks (or assured activities) that local district teachers develop and promise to teach. The significant tasks are aligned to standards and assessment specifications. District curriculum authors also develop assessments for all to use when implementing the curriculum. Results of more than 15 years of implementation show that all districts that have developed curriculum using this model, and ensured implementation, have had significant improvement on their test scores. Implications for teachers, principals, and central office staff are given at the end of the article. © The Author(s) 2013.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/057-464-358-258-828 tex.type: [object Object]
Keywords: Curriculum; Student achievement results; dept.edl

Culturally responsive leadership: best practice in integrating immigrant students - Magno, Cathyrn S; Schiff, Margo (Intercultural Education, 2010)
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-598-856-404-821 tex.type: [object Object]
Keywords: dept.edl

School Counseling Programs Identifying Academic Development Needs - Parzych, Jennifer L.; Generali, Margaret; Yavuz, Olcay (Journal of Education, 2021)
This study examined student, parent, and faculty perceptions of academic development needs and related comprehensive school counseling program services from four urban middle and high schools. Participants (n = 1,032) completed a survey designed to assist schools in planning and evaluating their career and college readiness programs, and exploring perceived student support needs. Statistically significant differences were observed in stakeholder perceptions among 12 identified interventions that support improved academic development, through factorial analysis of variance (ANOVA) and pairwise comparisons analysis. Findings provide valuable information about prioritizing student academic counseling services strategically and effectively, to meet program needs of students in high-poverty schools.
1 citations (Crossref) [2023-10-31]
Keywords: academic development; college readiness; dept.csp; dept.edl; peer-reviewed; poverty; school counselors

School Leadership for Learning: Learning Theory to Improve Professional Practice - Gregory, Jess L.; Ben-Avie, Michael; Billups, Felice; Grassetti, Mary; Hesser, Tiffany; Lawlor, Jennifer Lynne; Martone, Drey; Maykel, Cheryl; Minkos, Marlena L.; Paslov, Linda; Trombly, Christopher; Tucker, Lauren; et al. (Jess L. Gregory, 2021)
Keywords: Educational leadership; School administrators; Handbooks; manuals; etc; In-service training; School administrators; In-service training; Teachers; dept.edl; dept.sed; faculty_collection

A quantitative exploration of students’ mindsets and behaviors: A whole child academic, emotional, and career development - Yavuz, Olcay (International Journal of Educational Reform, 2019)
The demands of the 21st century require a systemic and collaborative perspective to promote the long-term development and success of all children. The purpose of this international comparative study is to investigate students’ mindsets and behaviors for school, college, and career success. The results revealed that there are key factors significantly impact on the students’ perceptions on academic, emotional, and career development. The author hopes this study will add to the limited existent research on educating the whole child. Also, this study should assist in future policies and practices by providing explorative analyses for students’ attitudes or beliefs for achieving their college and career goals.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-886-341-738-646, pop00313 tex.type: [object Object]
Keywords: academic success; career readiness; dept.edl; emotional development; peer-reviewed

A systematic approach to exploring college and career readiness program needs within high-poverty urban public schools - Yavuz, Olcay; Parzych, Jennifer; Generali, Margaret (Education and Urban Society, 2019)
This quantitative correlational study was designed to investigate whether the core and enrichment college readiness program needs within high-poverty urban schools significantly varied with respect to grade level and stakeholder perceptions. Statistically significant differences were discovered in parent, student, and faculty perceptions in core and enrichment programs related to high-poverty urban school needs. The findings provide valuable information about how to design student academic and counseling services strategically and effectively to increase college and career readiness for low-income, urban students. Findings also provide effective strategies for school leaders, educators, and counselors regarding urban school college and career readiness program needs so that resources can be intentionally distributed in areas of greatest importance.
2 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000463178900001, lens.org/043-148-982-388-631, yavuzSystematicApproachExploring2019a tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: accountability; change; dept.csp; dept.edl; peer-reviewed; school improvement; school reform; urban education

Applying SERVQUAL: Using service quality perceptions to improve student satisfaction and program image - Gregory, Jess L. (Journal of Applied Research in Higher Education, 2019)
Purpose: Austerity approaches in higher education require choosing the highest leverage strategies of increasing student satisfaction. Attending to student perceptions of program/service quality (SERVQUAL) is a means to identify areas that have the greatest return on investment. The paper aims to discuss these issues. Design/methodology/approach: This study explores how a program has applied the SERVQUAL model and survey to identify areas for growth. Findings: The survey of 57 students in a cohort-based doctoral program demonstrated the smallest gaps (highest satisfaction) with the domains of empathy (1.33) and responsiveness (1.30) and the lowest with reliability (2.03), tangibles (1.97) and assurance (1.90). Practical implications: While not all of the five dimensions are within the purview of a program to address (some may require funding that is determined at a college or university level), many of the gaps can be addressed by adopting procedures and policies that increase transparency so that students can moderate their expectations and faculty and staff can provide reliable information. Additionally, the use of the SERVQUAL model provided this program with specific, actionable information that could be used to improve the program. Originality/value: The study includes a review of studies that have applied the SERVQUAL model in higher education. The application of SERVQUAL to a cohort-based doctoral program to identify program improvements and steward program image fits into a gap in the extant literature. © 2019, Emerald Publishing Limited.
14 citations (Crossref) [2023-10-31] tex.ids: lens.org/000-458-242-452-814, pop00269 tex.type: [object Object]
Keywords: Market-driven forces in education; SERVQUAL; Service quality; Student satisfaction; dept.edl; peer-reviewed

Editorial: Educational leadership and social justice - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2019)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Preparing perform and impact ready school leaders for improving urban school success - Yavuz, Olcay; Gülmez, Gülçin (Research in Educational Administration & Leadership, 2018)
In an effort to develop and support high quality urban school leaders, this study examined what factors affect pre-service urban school leaders’ perception of preparedness for performing instructional leadership activities. The findings revealed that participating in a leadership training program is the only significant factor that predicts urban educators’ scores on instructional leadership readiness measures. By examining perception of preparedness of aspiring urban school leaders the findings contribute to our understanding about some perspectives to prepare and develop urban school leaders solve large and complex problems related to the curriculum, instruction and assessment. Implications for preparing performance ready school leaders in high need urban schools are further discussed. © Official Publication of EARDA-Turkish Educational Administration Research and Development Association.
0 citations (Crossref) [2023-10-31]
Keywords: Leadership training; Perception of preparedness; Urban leadership; dept.edl; peer-reviewed

School leadership training: Are we preparing future talent managers? - Yavuz, Olcay; Madonia, Peter; Abolafia, Victoria M. (Uluslararası Liderlik Eğitimi Dergisi, 2018)
Effective leadrship talent management practices are important components of successful organizations. This correlational quantitative study is designed to inform educational leadership training programs in their work to revise their curricula and to utilize the candidates’ perception data to ensure successful program delivery and outcomes. Particularly, the findings of this study aim to inform educational leadership preparation practices on developing talent managers who can recruit, hire, retain, and support the most talented and high qualified teachers, as well as support staff available in the education job market. Results indicate that after completing the first year of educational leadership training only around half of the aspiring school leaders felt performance or impact ready to serve as talent managers, in order to select and develop highly qualified educators to increase the success of all students. The findings also suggest the importance of understanding how various factors predict an individual’s perception of preparedness to perform talent management leadership activities. Therefore, the study results may serve to enrich conversations of educational leadership training programs, guide program evaluation efforts, and help ensure candidates in educational leadership programs are exposed to talent management and strategies in their coursework. This may help future school leaders clearly and purposefully apply their knowledge and skills.
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Perceptions of social emotional learning needs in high poverty schools - Generali, Margaret M.; Yavuz, Olcay; Parzych, Jennifer (Journal of Contemporary Administrative Science, 2018)
This paper explores the perceived social emotional learning needs of students in high poverty schools. Social emotional learning (SEL)is recognized within the literature as critical to success in school and in life. Emergingwork supports the acquisition of a SEL skillset within grades kindergarten through twelve ( K-12) schools. This survey examines the perceptions of social emotional needs as reported by students, parents and school faculty members across four different high poverty schools in the USA. Findings provide effective strategies and valuable data for school leaders, educators, and counselors in addressing the social emotional needs of urban students.
Keywords: dept.csp; dept.edl; peer-reviewed; ⛔ No DOI found

Urban tween talk about using mobile phones for learning - Arafeh, Sousan; Kuszpa, M; Weller, M; Mitchell, T (Mobile Learning: Perspectives on Practice and Policy, 2018)
There can be no doubt that mobile technologies are here to stay. Global mobile traffic grew 74 percent in 2015 alone, with 563 million devices and connections added – most of them tablets and Smartphones. This growth has been 4000-fold in the past 10 years and 400 million-fold in the past 15 years (Cisco, 2016). Mobile technologies permeate the lives of 21st century citizens as mainstays of organizational and institutional day-to-day operations, commerce, and communication and as tools used to support individuals' personal, social, and career responsibilities. In both the corporate and educational worlds, e- and m-learning and marketing with mobile technologies are moving forward at breakneck speed with, in many cases, a blurring of traditional sector boundaries. As neither the technology nor the uses are static, exploring practices and policies that underpin this quickly shifting mobile technology context is crucial for ensuring its intelligent, purposeful, and equitable use. This edited book provides a venue for researchers to share their work on mobile learning with a focus on uses for mobiles in informal settings and PK-20 classrooms, language learning, mobile gaming, leadership and policy issues, and what mobile learning in the future may be. It assists researchers and educators to consider and answer questions such as: What is "mobilelearning" today How can mobiles be used to enable learning How is mobile learning crossing or connecting economic, social, and/or cultural sectors How do specific cultural practices with media influence mobile learning (e.g
Keywords: dept.edl

Access versus success: Services for students with disabilities in postsecondary education. - Sassu, Kari (Journal of Educational Leadership and Policy Studies, 2018)
Keywords: dept.csp; peer-reviewed; ⛔ No DOI found

Attitudinal instrument development: Assessing cognitive, affective, and behavioral domains of teacher attitudes toward teaching all students - Gregory, Jess L; Noto, Lori A (Cogent Education, 2018)
Despite their entree into the physical space of general education classrooms and the expected instruction of the core academic standards, students with disabilities may still be excluded. Successful inclusion requires a commitment at district, school and classroom level. The attitude of the general education teacher toward the inclusion of students with disabilities is a critical component in the success of inclusionary efforts. The attitudes toward teaching all students (ATTAS-mm) instrument are a nine-item scale with strong reliability and validity that measures educator attitudes. The three subscales: believing all students can succeed in general education classrooms (cognitive), developing personal and professional relationships (affective), and creating an accepting environment for all students to learn (behavioral) explain nearly 80% of the variance in scores. The unstandardized Cronbach alpha for the entire ATTAS-mm scale was 0.83. The three subscales also demonstrated acceptable reliability values (Cognitive, 0.72; Affective, 0.93; Behavioral, 0.84). With strong internal reliability and validity established through a panel of experts and alignment with cognitive psychology literature, the ATTAS-mm was determined to be a valid and reliable instrument for measuring the attitudes toward teaching all students. © 2018 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/178-902-357-221-200 tex.type: [object Object]
Keywords: ATTAS-mm; dept.edl; inclusion; instrument development; peer-reviewed; special education; teacher attitudes

Culturally responsive practice and the role of school administrators - Minkos, Marlena L.; Sassu, Kari A.; Gregory, Jess L.; Patwa, Shamim S.; Theodore, Lea A.; Femc-Bagwell, Michele (Psychology in the Schools, 2017)
In recent years, student populations within public schools in the United States have become increasingly diverse, both culturally and linguistically, and are projected to continue to grow in diversity in the future. Consequently, educators must be prepared to support the needs and education of students with multicultural backgrounds who may differ from them. School administrators play an important role in creating safe, accepting school environments and guiding the education of diverse student populations. However, there is a need for additional guidance for school leaders in cultivating schools that promote equity for all students. Using the National Policy Board for Educational Administration (NPBEA) Professional Standards for Educational Leaders as a guiding framework, this paper provides practical suggestions regarding culturally responsive strategies and practices that school administrators might employ in leading diverse school communities.
15 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000415935300007, lens.org/072-893-262-948-380 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: culturally responsive practice; dept.csp; dept.edl; diversity; educational leadership; peer-reviewed

Trust relationships in schools: supporting or subverting implementation of school-wide initiatives - Gregory, Jess L. (School Leadership & Management, 2017)
This article explores trust relationships in schools that involve disparities in power. Trust is a key factor in developing a positive school culture and strong leadership in schools. Even with the flattening of hierarchies through more distributive models of leadership, disparities in power exist and they influence the trust relationships in schools. Through both French and Raven’s and Follett’s conceptualisations of power, five brief autobiographical stories about trust in schools are deconstructed. Lessons for leadership are gleaned from the power relationships in the autobiographical stories of trust shared by public school educators. In addition, general recommendations are offered that are relevant for all levels of school leadership including but not limited to the instructional coach, the curriculum supervisor, the building principal, and the classroom teacher.
8 citations (Crossref) [2023-10-31]
Keywords: Follett; French & Raven; Trust; change leadership; dept.edl; educational leadership; power

Improving student achievement through strengthening principal and school counselor partnership - Yavuz, Olcay; Cayirdag, Nur; Dahir, Carol; Gümüşeli, Ali İlker (International Journal of Educational Reform, 2017)
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-647-036-070-16X, pop00220 tex.type: [object Object]
Keywords: dept.edl; peer-reviewed

School principal perceptions of the school counsellor's role: Traditional or transformed? - Yavuz, Olcay; Dahir, Carol; Gumuseli, Ali Ilker (Journal of Educational Leadership, Policy and Practice, 2017)
There is a continued emphasis on the importance of building collaborative working relationships between school principals and counsellors to address the growing academic, career and college readiness, and social-emotional needs of students in K-12 schools. This study explored and analysed 1466 school principals' perceptions around important school counselling priorities, perceptions, and activities that are carried out in Turkish public and private schools. The study additionally explored school principals' expectations of school counsellors' roles and responsibilities as aligned with traditional and transformed school counselling programmes and practices. This study may be of value to school leaders, policy makers and educators interested in revising and improving their school counselling services to meet the complex academic and counselling needs of students in contemporary schools.
Keywords: dept.edl; ⛔ No DOI found

Attitudes of Croatian and Polish elementary school teachers towards inclusive education of children with disabilities - Cwirynkalo, Katarzyna; Kisovarivanda, Tamara; Gregory, Jess L; Żyta, Agnieszka; Arciszewska, Aleksandra; Zrilic, Smiljana (Hrvatska Revija za Rehabilitacijska Istraživanja, 2017)
Inclusive education has been gaining increasing attention from governments throughout the world. Croatia and Poland, two European Union members that ratified the Convention on the Rights of Persons with Disabilities, have been working on issues related to improving the quality of education of children with special educational needs. The aim of this article was to explore the attitudes of Croatian and Polish elementary education teachers towards inclusion of these children in regular classes. The sample consisted of 98 elementary education teachers from Croatia (N=50) and Poland (N=48). A diagnostic survey based on the Teacher Attitudes Toward Inclusion Scale (TATIS) (Cullen, Gregory, & Noto, 2010) was used. The instrument allows measurement of three main components of attitudes: teacher perceptions of students with mild to moderate disabilities (POS), their beliefs about the efficacy of inclusion (BEI), perceptions of professional roles and functions (PRF), as well as their general attitudes towards inclusion. We found that Polish teachers received significantly higher scores on two subscales: POS and BEI. We also found that age and place of living influenced the attitudes of teachers in the two groups. Implications for practice are discussed. © 2017, University of Zagreb, Faculty of Political Sciences. All rights reserved.
Citation Key Alias: lens.org/154-714-360-054-192 tex.type: [object Object]
Keywords: Children with disabilities; Inclusive education; Teachers’ attitudes; dept.edl; ⛔ No DOI found

Mindfulness as a prerequisite to effective leadership; exploring the constructs that foster productive use of feedback for professional learning - Day, Danette V; Gregory, Jess L (Interchange, 2017)
This paper proposes a model that integrates mindfulness, ego, and mindset as filters of the information available for professional learning. The paper explores connections between mindset, ego, and mindfulness that promote or inhibit an educator’s ability to use feedback for learning. A leader’s commitment to creating spaces for meaningful use of all types of feedback promotes a school climate that encourages risk taking in learning. Mindfulness, the cultivation of the ability to pay attention to the present moment non-judgmentally, is a prerequisite skill to the effective delivery and use of feedback to promote professional learning. The development of mindfulness requires practice of a method and the continual application of mindfulness to remain open to learning from feedback. © 2017, Springer Science+Business Media B.V.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-616-943-494-687 tex.type: [object Object]
Keywords: Effective leadership; Ego; Feedback; Mindfulness; Mindset; Professional learning; dept.edl

Instructional scaffolding to promote an autonomous learner - Gregory, Jess L (Preparing Pre-Service Teachers for the Inclusive Classroom, 2017)
An autonomous learner has developed an intrinsic motivation that drives him or her to pursue learning for the inherent satisfaction and enjoyment that stems from the acquisition of knowledge. This chapter presents strategies for teachers to develop a classroom of more autonomous learners. In addition to some strategies and sequencing of activities to maximize their impact, the chapter presents Universal Design for Learning as a framework for thinking about all teaching and ways to apply differentiated instruction to meet the needs of all learners. While there is a focus on the experience of a novice teacher, the content of this chapter is relevant for all educators looking to reinvigorate their practice to empower students to be more in command of their own learning.
Citation Key Alias: lens.org/149-445-063-289-055
Keywords: dept.edl